The impact of E-CRM on customer loyalty in the airline industry: the mediating role of customer experience - Nafez Ali; Maha Alfayez (Cogent Business & Management, 2024)
In today's highly competitive airline industry, understanding the factors that influence customer loyalty is paramount for airline companies seeking to maintain a competitive edge. This study investigates the impact of Electronic Customer Relationship Management (E-CRM) on customer loyalty within the context of the airline industry, with a specific focus on the mediating role of customer experience. By examining how E-CRM strategies influence customer loyalty and the underlying mechanisms through which customer experience mediates this relationship, this research aims to provide valuable insights for airline companies striving to enhance customer satisfaction and retention. Using a quantitative research approach, the study targeted Royal Jordanian travelers as the primary research participants. A sample of 386 individuals who have flown with Royal Jordanian Airlines was selected using a convenience sampling method. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) Version 26. This study reveals that E-CRM dimensions have a statistically significant impact on customer loyalty and experience. Furthermore, the findings show that customer experience mediates the relationship between E-CRM dimensions and customer loyalty. In light of these findings, this study recommends focusing on improving the effectiveness and reliability of the Royal Jordanian Airlines website. This includes initiatives aimed at improving a website's efficiency, strengthening security measures, and ensuring a high level of dependability to increase customer loyalty.
Keywords: C81; L93; M31; O33; 650; E-CRM; customer loyalty; customer experience; airline industry; website optimization